Keterampilan Pedagogik Guru Pada Mata Pelajaran Al-Qur’an Hadist di MIS Riyadlatul Uqul Kranggan - Rasta Nugroho Saputra; Reffi Kesuma Nufadhilah; Rizka Nur Azizah; Rizky Khoirunisa; Rizky Maulana Adi Pangestu (Social Science Academic, 2024)
This study aims to examine the pedagogical skills of Al-Qur'an Hadith subject teachers at MIS Riyadlotul Uqul Kranggan in utilizing social media. The importance of this research lies in the rapid development of ICT which has an impact on the world of education, especially learning Al-Qur'an Hadith. The method used is a qualitative approach with interview techniques with al-Qur'an Hadith subject teachers. The results of the interview were analyzed using the Miles and Huberman technique, including data reduction by recording and analyzing data findings, presenting data in narrative form, and drawing conclusions. The findings from the interviews show that teachers' pedagogical skills in utilizing ICT include the use of media, online learning resources, ICT-based assessments, and developing students' digital literacy, although there are infrastructure constraints, and teacher training using ICT in learning. The problem limitation is to focus on the pedagogical skills of Al-Qur'an Hadith subject teachers.